Fostering adolescents' coping skills: An action approach - Isrealashvili, Moshe (Canadian Journal of Counselling and Psychotherapy, 2007)
Following a description of differences between the more common approaches to coping skills acquisition and an action theory approach, the potential implementation of action theory with people who experience transitional states is discussed. Specifically, adolescents in Israel are confronted by making the transition to military life following secondary school. It is suggested that action theory offers a comprehensive strategy for counselling persons who are confronting a stressful episode in life through a more detailed and socially embedded collaboration between the counsellor, the person (client), and peers. By doing so, the benefits of other common approaches to coping skills acquisition are gained, along with an enriched and expanded program for counselling people (adolescents) who are facing stressful life events.